Do Male and Female Students Represent Their Experiences Differently? : A Transitivity Analysis of Students’ Texts - Wildan Nurul Aini (Ma'soem University, 2021)
This study explores the way male and female students use process types in recount texts to represent their experiences. To attain these goals, the qualitative design was employed and the main data were the students’ recount texts. The texts were then analysed using the transitivity framework, proposed by Halliday (1994), to unveil the representation of experiences by male and female students. The results indicate that the students from both genders have a quite identical way of representing their experiences. Both groups use a lot of Material, Mental and Relational-Attributive processes. The domination of these processes is high likely to be influenced by the social function and generic structure of Recount texts. Thus, in terms of process types, instead of gender, the genre has more influence on how students represent their experiences.